Long‐term safety of icatibant treatment of patients with angioedema in real‐world clinical practice. Issue 6 (13th March 2017) - Zanichelli, A.; Maurer, M.; Aberer, W.; Caballero, T.; Longhurst, H. J.; Bouillet, L.; Fabien, V.; Andresen, I.; ,
Abstract: The Icatibant Outcome Survey (IOS) is an observational study monitoring safety and effectiveness of icatibant in the real‐world setting. We analyzed safety data from 3025 icatibant‐treated attacks in 557 patients (enrolled between July 2009 and February 2015). Icatibant was generally well tolerated. Excluding off‐label use and pregnancy, 438 patients (78.6%) did not report adverse events (AEs). The remaining 119 (21.4%) patients reported 341 AEs, primarily gastrointestinal disorders (19.6%). Of these, 43 AEs in 17 patients (3.1%) were related to icatibant. Serious AEs (SAEs) occurred infrequently. A total of 143 SAEs occurred in 59 (10.6%) patients; only three events (drug inefficacy, gastritis, and reflux esophagitis) in two patients were considered related to icatibant. Notably, no SAEs related to icatibant occurred in patients with cardiovascular disease, nor in those using icatibant at a frequency above label guidelines. Additionally, no major differences were noted in AEs occurring in on‐label vs off‐label icatibant users.